2017
DOI: 10.21432/t24c82
|View full text |Cite
|
Sign up to set email alerts
|

Gadgets in the Gymnasium: Physical Educators’ Use of Digital Technologies | Les gadgets au gymnase : l’utilisation des technologies numériques par les enseignants en éducation physique

Abstract: This article highlights results from a recent study that investigated Atlantic Canadian physical educators' adoption and implementation of various digital technologies. Employing a mixed-methods research design (survey participants, n = 206; focus group participants, n = 12), the research intended to provide a clear overview of physical educators' implementation of digital technologies-as well as an account of the factors that may enable or limit their use. Results suggest that some digital technologies are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…This includes, for example, a high time requirement or lack of training. A total of 13 studies presented results on this topic: six were quantitative in nature (Aktag, 2015;Bisgin, 2014;Fernández-Batanero et al, 2019;Hill & Valdez-Garcia, 2020;Legrain et al, 2015;Rojo-Ramos et al, 2020), four adopted a qualitative approach (Baek et al, 2018;Marttinen et al, 2019Marttinen et al, , 2020Steinberg et al, 2020), and two used a mixed-methods design (Kretschmann, 2015;Robinson & Randall, 2017).…”
Section: School Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes, for example, a high time requirement or lack of training. A total of 13 studies presented results on this topic: six were quantitative in nature (Aktag, 2015;Bisgin, 2014;Fernández-Batanero et al, 2019;Hill & Valdez-Garcia, 2020;Legrain et al, 2015;Rojo-Ramos et al, 2020), four adopted a qualitative approach (Baek et al, 2018;Marttinen et al, 2019Marttinen et al, , 2020Steinberg et al, 2020), and two used a mixed-methods design (Kretschmann, 2015;Robinson & Randall, 2017).…”
Section: School Conditionsmentioning
confidence: 99%
“…They found that the lack of resources was often a major reason for not including digital media in PE. Specifically, regarding barriers influencing the use of digital media, teachers named class size as well as lack of access to media, support, time, expertise, and budget (Hill & Valdez-Garcia, 2020;Legrain et al, 2015;Robinson & Randall, 2017). The given resources also influenced the way in which digital media were used in the classroom (Marttinen et al, 2020).…”
Section: School Conditionsmentioning
confidence: 99%